2020
DOI: 10.1186/s41182-020-00229-4
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants species used by herbalists in the treatment of snakebite envenomation in Uganda

Abstract: Background: There are high mortality and morbidity rates due to poisonous snakebites globally with sub-Saharan Africa having some of the highest cases. However, traditional medicine practitioners (TMP) have been treating snakebites in Uganda for long despite the fact that few studies have been conducted to document such vital and rich indigenous traditional knowledge before it is lost. This study aimed to document the medicinal plant species used by experienced TMP in treating snakebite envenomation in selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
(28 reference statements)
1
24
1
Order By: Relevance
“…The species listed are mainly herbs and shrubs collected from savannas and fallow lands. On the one hand, many previous studies have mentioned herbs as the most used in the treatment of snakebite envenomation, as they occupy a prominent place in many traditional health care systems (Butt et al 2015, Okot et al 2020. The widespread use of herbs in treatment of ailments by local communities may be linked to the extensive diversity and inexpensive accessibility of herbaceous plants in their environment (Uniyal et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The species listed are mainly herbs and shrubs collected from savannas and fallow lands. On the one hand, many previous studies have mentioned herbs as the most used in the treatment of snakebite envenomation, as they occupy a prominent place in many traditional health care systems (Butt et al 2015, Okot et al 2020. The widespread use of herbs in treatment of ailments by local communities may be linked to the extensive diversity and inexpensive accessibility of herbaceous plants in their environment (Uniyal et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, research shows that literacy levels of people determined the mode of treatment [30]; the less educated preferred traditional methods of treatment where as the well educated preferred modern methods of health care. Research over the years has shown low literacy levels among research respondents: [31,32,33,26].…”
Section: Education and Plant Knowledgementioning
confidence: 99%
“…It is mentioned that the Quran (Holy Moslem scripture), illustrates the importance of plants for medicinal benefits [42]. Therefore, prayer is an essential ingredient in traditional healing practices among many societies [31] in addition to use of herbal remedies.…”
Section: Religion and Plant Knowledgementioning
confidence: 99%
“…The disparity in plant usage across the countries could be due to the choice of medicinal plants utilized by traditional medicine practitioners is based on complex mechanisms [100]. Plant scent and appearance (such as possession of aerial roots reminiscent of a snake) may influence the choice of a plant used in snakebite therapy [35,101,102]. In addition, the differences in plant usage are more likely due to the climatic and soil variations that is known to account for variations in species distribution and phytochemical composition of the same plant species in different geographical locations [103].…”
Section: Ethnomedicinal Plants Used In Treating Snake Poisoning Across East African Countriesmentioning
confidence: 99%